2001
DOI: 10.1046/j.1365-2265.2001.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of insulin resistance in patients with adrenal incidentaloma by surgical resection

Abstract: High prevalences of disturbed glucose tolerance, insulin resistance and hypertension were found among the patients with non-functioning adrenocortical tumours. Adrenocortical adenoma may be one of the risk factors for insulin resistance that is believed to induce disturbed glucose tolerance and/or hypertension. Therefore, it is useful to evaluate insulin resistance for the patients with adrenal incidentalomas since results are likely to be helpful in deciding whether to remove the tumour by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 25 publications
(36 reference statements)
3
93
2
2
Order By: Relevance
“…Midorikawa and cols. had demonstrated an incidence of insulin resistance, disturbed glucose tolerance and elevated blood pressure in patients with non-functioning adrenal adenoma and subsequent improvement in these metabolic states after removal of the tumors (21). Fernández-Real and cols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Midorikawa and cols. had demonstrated an incidence of insulin resistance, disturbed glucose tolerance and elevated blood pressure in patients with non-functioning adrenal adenoma and subsequent improvement in these metabolic states after removal of the tumors (21). Fernández-Real and cols.…”
Section: Resultsmentioning
confidence: 99%
“…Many patients with incidental nonfunctioning adrenal adenoma have increased risk of obesity, impaired glucose tolerance and dyslipidemia (11)(12)(13). We aimed to investigate the relationship between thyroid function, serum lipids and insulin resistance in patients with nonfunctioning adrenal incidentaloma.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of blood pressure, obesity, metabolic abnomalities, collagen and bone turnover markers was observed after adrenalectomy in patients with subclinical Cushing's syndrome (51,66,67). In particular, Midorikawa et al (89) demonstrated an improvement in systolic blood pressure and insulin resistance after adrenalectomy both in patients with subclinical Cushing's syndrome and in those with non-functioning cortical adenoma, but not in patients with non-cortical tumors (89). Cross-sectional and case-control studies indicate that the degree of metabolic abnormalities in patients with adrenal incidentalomas is directly related to the severity of the hypercortisolism (94, 118, 121 -124).…”
Section: Hormone Productionmentioning
confidence: 98%
“…Whether these features, which are typical of the metabolic syndrome, will have an impact on the long-term morbidity of patients with subclinical Cushing's syndrome remains to be determined. Long-term perspective studies are lacking; however, an amelioration of clinical or biochemical abnormalities in patients with subclinical hypercortisolism after surgery has been reported (42,51,53,66,67,(88)(89)(90). Improvement of blood pressure, obesity, metabolic abnomalities, collagen and bone turnover markers was observed after adrenalectomy in patients with subclinical Cushing's syndrome (51,66,67).…”
Section: Hormone Productionmentioning
confidence: 99%
“…However, so far, no studies specifically investigated the possible association between the pre-surgical biochemical diagnosis of SH and the subsequent presence of post-surgical hypocortisolism. The prevalence of post-surgical hypocortisolism in patients, with and without SH, who underwent unilateral adrenalectomy for AI, varies depending on the criteria used to diagnose SH (12)(13)(14)(15)(16)(17)(18). In addition, most studies considered only post-surgical basal cortisol level or the presence of symptoms suggesting adrenal failure as a diagnostic tool for post-surgical hypocortisolism (12,15,17,18).…”
Section: Introductionmentioning
confidence: 99%